Halacarus socius (Acari: Halacaridae), description of the male and diagnoses of species of the Halacarus actenos group - Bartsch, Ilse (Zootaxa, 2011)
Amongst the about a dozen halacarid species from a shore of Mauritius, the genus Halacarus was represented by a single species, Halacarus socius Bartsch, 1992. The species was once described on the basis of females collected on Moorea, Society Islands, Pacific Ocean, now a description of the male is added and that of the female supplemented. Halacarus socius seems to be wide-spread in the Indo-Pacific region. Halacarus tritoni Otto is a synonym. Halacarus socius is a member of the H. actenos group, a group characterized by the combination: posterior dorsal plate absent in both females and males, ocular plates small or lacking, with or without a cornea, apodemes of anterior and posterior epimeral plates long, female genitoanal plate with rather uniform cerotegumental cover and two pairs of perigenital setae adjacent to the genital opening, one pair (rarely two pairs) of perigenital setae anterior to the genitoanal plate, one or two bipectinate setae on tibia II, no tines on shaft of claws but paired claws often with tines on the accessory process. Species attributed to this group are diagnosed.